Characteristics and surgical invervention of ovarian torsion in pregnant compared with nonpregnant women. Issue 24 (12th June 2020) - Wu, Wei-Fang; Wang, Zhen-Hong; Xiu, Ying-Ling; Xie, Xi; Pan, Mian
Abstract : Abstract: The aim of our study was to compare the clinical and surgical characteristics of pregnant and nonpregnant women with surgically verified ovarian torsion, as well as the differences among 3 trimesters during pregnancy. We conducted a retrospective study of patients diagnosed with surgically proven ovarian torsion in our hospital from January 2012 to June 2018. The clinical characteristics, surgical procedure, pathologic outcomes, and trimesters of pregnancy were analyzed. Thirty-three pregnant and 72 nonpregnant patients diagnosed with surgically proven ovarian torsion were assessed during the study period. The most common presenting symptom in both groups was abdominal pain (90.2% and 99.0%, respectively). The median time from admission to surgery was shorter in pregnant patients than nonpregnant patients (5.3 compared with 47.7 hours, P  < .001). Pregnant patients had a higher number of twists than nonpregnant patients (median of 2 compared with 1, P  < .01). Benign cyst was the most common cyst causing ovarian torsion in both groups, and luteum cyst was more common in the pregnant group. The mean size of ovarian cyst in pregnant patients was much smaller in the third trimester than the first and the second trimesters (6.6 ± 2.0, 8.4 ± 2.1and 8.1 ± 1.5 cm, respectively; P  = .097). Cystectomy performed in the third trimester was more frequent compared with the other 2 trimesters (77.8%, 26.7%, and 22.2%, respectively; P  = .021). Abdominal pain is the most common feature of ovarian torsion. Clinical presentation of ovarian torsion is relatively similar between pregnant and nonpregnant women, and among different trimesters. The tumor size was smaller in the third trimester of pregnancy than the other 2 trimesters of pregnancy. Cystectomy performed in pregnant patients is more during the third trimester compared with the other 2 trimesters.